Stochastic Inversion in Determining the Distribution of Petroleum Carrying Sandstones in the "JS" Field of the South Sumatra Basin - Situmorang, Johannes Kurni Bintang Awan; Tampubolon, Gindo; Juventa, Juventa; Suhban, Muhammad (JURNAL GEOCELEBES, 2024)
The "JS" field is a field located in the South Sumatra Basin, where the field has good prospects for the distribution of petroleum-bearing sandstone. The target of this research is the Air Benakat formation. This research uses the stochastic seismic inversion method to determine the probability of finding petroleum in sandstone. Stochastic seismic inversion has the advantage that it can overcome thin layers and can reduce existing data misalignments. So stochastic inversion can overcome the shortcomings of other seismic inversions, especially model-based seismic inversion which is the initial model for stochastic seismic inversion. Stochastic seismic inversion produces several realizations by showing uncertainty so as to get results that are close to the actual situation. Probability map of oil-bearing sandstones located in the north and east of the study area. with the slice results obtained for the acoustic impedance range of 8517-9051(m/s)*(g/cc) and oil sand probability with a value range of 0.61-0.78%.